Children behaving badly? : peer violence between children and young people - Barter, Christine; Berridge, David (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
This publication directly addresses the complexity of peer violence from a range of disciplines and perspectives. The book provides important insights into theoretical understanding of the issue and produces significant and far-reaching implications for policy and practice developments.
Peer violence in different contexts -- Understanding dimensions of "peer violence" in preschool settings : an exploration of key issues and questions / Jane Brown -- Understanding why children and young people engage in bullying at school / Helen Cowie -- Sibling abuse and bullying in childhood and adolescence : knowns and unknowns / Paul B Naylor, Laurie Petch, and Jenna Williams -- Young people, gangs, and street-based violence / Tara Young and Simon Hallsworth -- Peer violence in provision for children in care / Andrew Kendrick -- Different forms of peer violence -- Young men, violence and racism / Les Back -- Partner exploitation and violence in teenage intimate relationships : a thoroughly gendered affair / Christine Barter -- Children and young people with harmful sexual behaviours / Simon Hackett -- Homophobia and peer violence / Ian Rivers -- Understanding peer violence -- Impact of child maltreatment and domestic violence / Veronica Herrera and Jeffrey Stuewig -- Media representations of youth violence / Sharon L Nichols -- Boys, girls, and performing normative violence in schools : a gendered critique of bully discourses / Jessica Ringrose and Emma Renold -- Responding to peer violence -- Bullets, blades, and mean streets : youth violence and criminal justice failure / Peter Squires and Carlie Goldsmith -- Delivering preventive programmes in schools : identifying gender issues / Nicky Stanley, Jane Ellis and Jo Bell -- Conclusion / David Berridge and Christine Barter.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Children -- Institutional care; Children -- Violence against; Peer pressure in children; Children and violence; Violence in children; Bullying; Pression des pairs chez l'enfant.; Enfants et violence; Violence chez l'enfant.; Intimidation; Bullying; Children and violence; Children -- Institutional care; Children -- Violence against; Peer pressure in children; Violence in children; Pesten; Geweld; Kinderen; Adolescenten